Evaluation Method for Science and Technology Performance on Energy Conservation and Emission Reduction - Zhao, Lin-Jia; Zeng, Wei-Hua; Zhang, Jia-Rui; Wang, Jin-Nan; Jiang, Hong-Qiang (Journal of Environmental Accounting and Management, 2026)
the different meanings and measures. We agree with Odum (1996) that